Sprogbrug og sprogsyn hos flertal og mindretal i den dansk-tyske grænseregion - Pedersen, Karen Margrethe (Nordiske Studier i Leksikografi, 2006)
Language use and language attitudes within the majorities and the minorities in the Danish-German border region. The Danish-German border region is characterised by a traditional linguistic diversity which is determined by national and regional affiliations and the status of the languages and dialects being used within the majorities and the Danish, German and North Frisian minorities. This article discusses the multidimensional linguistic pattern resulting from these groups’ use of Danish, the Danish dialect of Sønderjysk, German, Low German, North Frisian and the varieties South Schleswig Danish, North Schleswig German and Flensburg Petuh. And it clarifies that the minority languages ratified as such by the states most often are the minority members’ second language acquired outside the home and characterised by language contact phenomena. It also demonstrates that language nationalism has dominated the attitudes but is now being replaced by a language pluralism that corresponds to the diversity.